Monitoring and Evaluation of Water System as a Performance Indicator in Laeya Watershed Management, Southeast Sulawesi - La Baco Sudia (P2M Politeknik Pertanian Negeri Samarinda, 2023)
This research aimed to monitor and evaluate the performance of the Laeya Watershed, South Konawe Regency, Southeast Sulawesi Province. The method used a survey with a scoring technique using the flow regime coefficient, annual flow coefficient, sediment load, flood, and eater use index parameters based on the Regulation of the Minister of Forestry of the Republic of Indonesia Number 61 of 2014. The results showed that the performance assessment of the Laeya Watershed based on the aspect of water management was classified into a good class with a value of 73.05, with each of the sub-criteria flow regime coefficient (4.24 or very low class), annual flow coefficient (0.31 or medium class), sediment load (7.73 or low class), flooding (flood frequency 1 time/year or high class ) and water use index (4,228.60 or moderate class). The conclusion was that the performance of Laeya watershed management is quite good.